Tinjuan Hukum Islam Terhadap Proses Penentuan Hari Baik Sebelum Pernikahan (Studi Kasus Majelis Adat Aceh) - Anisatul Fajri; Muhammad Syuib; Boihaqi Bin Adnan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Determining an auspicious wedding day in traditional communities is a common practice, and is no exception in Acehnese society. Families typically determine a wedding day after a lengthy process, assessing the compatibility of the bride and groom. The purpose of this study was to determine and analyze how an auspicious day is determined before a wedding in Aceh and how Islamic law views this auspicious day. This study used qualitative research methods to obtain more in-depth data with a sociological approach. The results explain that: First: In determining the wedding day, village leaders use the method of calculating langkah (steps), raseuki (fortune), peuteumon (meeting), and mawot (death). If this calculation stops at raseuki or peuteumon, it is considered an auspicious day. Furthermore, in determining the right time for the wedding, some village leaders use the Teuku Cut Ali's predictions, hoping that the bride and groom will receive blessings and happiness in their married life. Second, the determination of the wedding day in Acehnese customs is a custom intended to select an auspicious day for the wedding. In Islamic law, determining an auspicious day for a wedding in Acehnese society is part of the 'urf, or good customs prevailing in the community that do not conflict with Islamic law.